Nusantara Hadith Study: A Study of Ahmad Hassan's Critical Thinking on the Hadith in the Book of Sual Answer - Iman, Hakim Nurul; Sa’adah, Dadah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study examines Ahmad Hassan Bangil's thoughts on hadith, which is one of the important discussions in the history of hadith in the archipelago. Ahmad Hassan Bangil is one of the charismatic and critical scholars who has ever been present in the archipelago. His contribution to Islam in Indonesia is very large. Known as an expert in debating and also skilled in writing his ideas in his books has skyrocketed his name. Although Ahmad Hassan did not write his work in the form of hadith science, his thoughts on hadith are very scattered in his books. One of his most phenomenal books is Sual Jawab, a book that contains problems in religion consisting of four volumes. In the book, it can be seen how Ahmad Hassan expresses his critical and progressive thoughts in hadith. To find out how Ahmad Hassan expresses his ideas, a qualitative method is needed, namely by analyzing the contents of his book using a library research approach. Then it can be found how Ahmad Hassan is more critical in explaining hadith. Where the figure of Ahmad Hassan always emphasizes to be more critical in taking a hadith, he always tries to find information that makes him sure that the hadith can be practiced or abandoned. If there is a hadith that is considered not to meet the requirements of a valid hadith, then he does not hesitate to abandon it.